2006
DOI: 10.1007/s10646-006-0084-2
|View full text |Cite
|
Sign up to set email alerts
|

Influence of pesticides and herbicides presence on phosphatase activity and selected bacterial microbiota of a natural lake system

Abstract: Phosphatase activities (cell-bounded phosphatases ''BP'' and freely dissolved phosphatases ''DP'') in water samples from a natural lake ''Laguna Grande'' (Antequera, Má laga, Spain) amended with 50 lg/ml of selected insecticides, herbicides and fungicide captan were studied under laboratory controlled conditions (temperature and agitation). Our data show that dissolved alkaline phosphatase was the enzymatic activity that contributed in higher proportion to total lake water samples phosphatase status. The prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 22 publications
0
7
0
1
Order By: Relevance
“…In mesocosms designed to simulate a tidal creek, chlorpyrifos applied at 10 µg L −1 increased heterotrophic bacterial abundance, while decreasing heterotrophic ciliate and flagellate (protozoan) abundance (DeLorenzo, Scott, and Ross, 1999). Similarly, parathion at 50 000 µg L −1 tended to increase abundance of heterotrophic bacteria in water samples collected from a natural lake (Lopez et al, 2006). However, another study revealed no significant effects of the pesticide on natural protozoan, bacterial, or fungal species in microcosms, even when concentrations exceeded water quality criteria three-fold (~12 000 µg L −1 ) (Pratt, Bowers, and Balczon, 1993).…”
Section: Specific Effects Of Pesticidesmentioning
confidence: 96%
See 4 more Smart Citations
“…In mesocosms designed to simulate a tidal creek, chlorpyrifos applied at 10 µg L −1 increased heterotrophic bacterial abundance, while decreasing heterotrophic ciliate and flagellate (protozoan) abundance (DeLorenzo, Scott, and Ross, 1999). Similarly, parathion at 50 000 µg L −1 tended to increase abundance of heterotrophic bacteria in water samples collected from a natural lake (Lopez et al, 2006). However, another study revealed no significant effects of the pesticide on natural protozoan, bacterial, or fungal species in microcosms, even when concentrations exceeded water quality criteria three-fold (~12 000 µg L −1 ) (Pratt, Bowers, and Balczon, 1993).…”
Section: Specific Effects Of Pesticidesmentioning
confidence: 96%
“…In another study of community level effects, endosulfan (at 1 µg L −1 ) increased phototrophic carbon assimilation, although diatom, dinoflagellate, algal species were significantly reduced (Downing et al, 2004). Aldin and lindane, at concentrations of 50 000 µg L −1 , resulted in increased heterotrophic bacterial abundance in samples taken from a natural lake (Lopez et al, 2006). In samples isolated from a tropical estuary system, bacterial abundance was reduced by endosulfan, DDT, and lindane at concentrations ranging from 2 to 2000 µg L −1 , with bacteria in the water column experiencing greater detrimental effects than those in the sediment (Rajendran, Rajendran, and Venugopalan, 1990).…”
Section: Specific Effects Of Pesticidesmentioning
confidence: 99%
See 3 more Smart Citations